KEWENANGAN PENYIDIKAN TINDAK PIDANA KORUPSI PADALEMBAGA PERKREDITAN DESA (LPD) - I NYOMAN SATYA WIRATAMA (Kerta Dyatmika, 2022)
Carrying out investigations and investigations into cases of criminal acts of corruption, especially those that occur in the Village Prediction Institution (LPD), is carried out by the Bali Regional Police. Based on the description of the background to the problem above, the following problems can be stated: how is the authority of investigators for criminal acts of corruption regulated at Village Credit Institutions (LPD) and what sanctions are imposed on Village Credit Institutions (LPD) that commit criminal acts of corruption The research method used is normative legal research. The approach method in this research is the statutory regulation approach. The data collection method in this researchwas carried out using a library study, which is a method of collecting data by searching and reviewing library materials (literature, research results, scientific magazines, scientific bulletins, scientific journals and so on). From the results of the discussion above, a conclusion can be drawn, namely: Theregulation of the authority of investigators of criminal acts of corruption at Village CreditInstitutions is regulated in Law no. 2 of 2002 concerning the State Police of the Republic of Indonesia, including to carry out investigations into criminal acts of corruption as regulated in Article 14 paragraph (1g) of Law No. 2 of 2002. Sanctions imposed on Village Credit Institutions (LPD) which commit criminal acts of corruption are being sentenced to imprisonment and paying a fine with the provision that if the fine is not paid, it will be replaced by imprisonment for three months. Meanwhile, customary legal sanctions are given based on the awig-awig of the Ungasan traditional village in the formof social sanctions where the perpetrator does not receive services from the traditional village officials and traditional community so that this is more torturous and makes the perpetrator feel deterred for the actions that have been committed so that there is little possibility of committing them. the same action.